VISUAL COMMUNICATION GRAPHIC GUIDANCE’S CONTENT OF SPECIAL ARTISTRY STYLE CREATION FOR YOUNG RHYTHMIC GYMNASTS - Krafte, Katrīna; Lāriņš, Viesturs; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The artistic evaluation of the competitive composition has a significant effect on the final result in rhythmic gymnastics. An important criterion of artistry is the ability of gymnasts to prove the idea and image of music-accompanied composition dynamically and emotionally. Thus, special artistry like imagery and its style is one of the determining tools for making an aesthetic impression, which accordingly affects the subjective evaluation of the composition. Considering the early specialization in rhythmic gymnastics, it is necessary to develop imagery of gymnasts already at the initial preparatory stage by using visual communication metaphoric graphic guidance. The aim of the research is to create a content of visual communication graphic guidance to develop the perception of special artistry styles for young rhythmic gymnasts (ages 4-6). To achieve the research goal scientific and specialized literature analysis and modelling methods were used. The graphic guidance was developed according to each style of special artistry, based on the visual communication design principles, illustrating the styles in the form of age-appropriate metaphors symbolized by animals, flowers, the environment, and other elements. In total, the content of 32 visual communication graphic guidance was developed.